Investigation of the relationship of apelin hormone response with some physiological parameters in Maedi-Visna infected sheep - BAYRAKTAR, B.; SAIT, A.; TAKMA, Ç; TEKCE, E. (Journal of the Hellenic Veterinary Medical Society, 2021)
In this study, the objective was to assess the serological characteristics of sheep, during lactation and pregnancy periods, and rams belonging to the Red Karaman and White Karaman–Kangal race infected with maedi-visna infection and body condition score (BCS) of ≤2, 3- 3.5 and ≥4 (high) and to analyse the relationship between the level of apelin and its secretion. Apelin level in the blood serum samples obtained from the jugular veinof the sheeps was determined using ELISA method. As a result of the analyses, it was determined that the level of apelin was statistically different between the races; between lactating sheep and pregnant sheep; and sheep and rams. There was no difference between the BCS groups (p > 0.05). Race and sex interaction as well as race, sex and BCS triple interaction effects were found significant (p < 0.05). It was observed that the sheep belonging to the White Karaman–Kangal race were 18 times more likely to be infected with the virus. A decrease in apelin level was observed in the sheep with infection, and it was found that the risk of infection was 0.37 times higher in rams than in lactating sheep (p < 0.05).